LTV, Macro Economics and ROE to Stock Return in Real Estate and Property Companies Listed on LQ 45 Period 2009 – 2017 - Hendrawan, Riko; Avitianti, Avi (International Journal of Engineering and Technology, 2018)
The purpose of this research is to exemine the effect of Loan to Value (LTV), exchange rate, Gross Domestic Product (GDP), Interest Rate and Return on Equity (ROE) to return of property stock that entered at LQ 45 in Indonesia Stock Exchange period 2009 - 2017. Using selected 5 Real Estate and Property Companies as research samples. Panel Data Regression Tehniques were use for this research. The result of this research is LTV partially has no significant effect on stock return, partial exchange rate has no significant effect on stock return, GDP partially significant effect of stock return interest rate partially does not have significant influence retun share, ROE partially significant effect of stock return and there is simultaneously significant influence between LTV, exchange rate, GDP, interest rate and ROE to stock return.Â Â